SUCCESSFUL THYROIDECTOMY IN SEVERE GRAVES’ DISEASE: A MODIFIED BLOCK-AND-REPLACE APPROACH - Rofii, Nursafinas; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Graves’ disease is the most common cause of autoimmune hyperthyroidism. In severe cases, thyroidectomy is required. The block-and-replace regimen helps achieve euthyroidism preoperatively, but perioperative thyroid instability remains a challenge, particularly in urgent surgical settings. CASE A 20-year-old Malay female with severe plaque psoriasis developed a painful goiter and severe thyrotoxicosis following Guselkumab treatment, necessitating carbimazole 30 mg daily. She was initially scheduled for radioactive iodine (RAI) therapy; however, two weeks after her fourth Guselkumab dose, just before her planned RAI, she had thyroid storm. Emergency management included Lugol’s iodine, high-dose propylthiouracil, corticosteroids, and cholestyramine. Due to recent iodine exposure, RAI was no longer a viable option, necessitating an alternative definitive treatment approach. Methimazole was increased from 20 mg to 25 mg twice daily, successfully lowering free T4 from 27 to 17 pmol/L. However, on the day before her scheduled thyroidectomy, severe hypothyroidism (TSH <0.01 mIU/L, T4 <5 pmol/L) was noted. To rapidly restore euthyroidism, she received a total of 300 mcg of levothyroxine overnight while continuing methimazole. This intervention raised her T4 to 8.3 pmol/L, ensuring safe surgical conditions while mitigating the risk of recurrent thyroid storm in this difficult-to-control case. CONCLUSION This case highlights the challenges of perioperative thyroid management in Graves’ disease. High-dose levothyroxine while maintaining methimazole facilitated urgent surgical clearance, balancing the risks of hypothyroidism and thyroid storm. This modified block-and-replace approach may be considered in select cases requiring time-sensitive surgical intervention.